Identifying the Subjective Experience of Learning Under High Performance Pressure - Viteri, Camila; Mokoena, Thandiwe; Mwangi, Grace (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: This study aimed to identify and explore the subjective emotional, cognitive, and social experiences of learners operating under high performance pressure within South African educational contexts.Methods and Materials: Using a qualitative design, this study adopted an interpretivist approach to understand the lived experiences of individuals facing intense performance expectations. Data were collected through semi-structured interviews with 24 participants drawn from universities and professional training programs across South Africa. Participants were selected purposively to ensure diversity in academic and occupational backgrounds, and interviews continued until theoretical saturation was reached. All interviews were audio-recorded, transcribed verbatim, and analyzed thematically using NVivo 14 software. Thematic analysis followed Braun and Clarke’s six-step method, and credibility was enhanced through member checking, peer debriefing, and reflexive documentation.Findings: Three overarching themes emerged from the data. First, emotional and cognitive responses to pressure revealed that anxiety, cognitive overload, and fluctuating motivation coexisted with resilience and growth mindset. Second, social and environmental influences demonstrated that institutional grading systems, peer comparison, family expectations, and digital monitoring amplified stress, while supportive instructor feedback and empathetic climates enhanced engagement. Third, coping, adaptation, and meaning-making highlighted that learners adopted both adaptive (mindfulness, reframing, time management) and maladaptive (avoidance, overstudying) strategies, with resilience and self-reflection transforming pressure into an opportunity for personal and academic development.Conclusion: Learning under high performance pressure simultaneously challenges and strengthens learners, shaping emotional resilience, motivation, and self-concept. The findings underscore the need for educational systems to balance high expectations with psychological safety, supportive pedagogy, and reflective learning practices to transform pressure into growth.